Investigating Male Presence at Antenatal and Choice of Place for Child Delivery in Ghana - Doegah, Phidelia Theresa (Frontiers in Public Health, 2019)
Male involvement in maternal health was introduced to improve and sustain maternal and child health in Ghana. The study utilized the 2014 Ghana Demographic and Health Survey data to investigate the relationship between male presence at antenatal and choice of place of childbirth among 1,167 males, 15–59 years. Descriptive and analytical statistical techniques were applied to the data. The binary logistic regression shows no association between male presence at antenatal and place of delivery (OR = 1.197; 95% CI = 0.808–1.773). However, age (OR = 2.647; 95% CI = 1.221–5.736, OR = 3.046; 95% CI = 1.345–6.896, OR = 3.513; 95% CI = 1.478–8.345), level of education (OR = 4.478; 95% CI = 1.412–14.1990, religion (OR = 0.473; 95% CI = 0.237–0.946), ethnicity (OR = 0.400; 95% CI = 0.182–0.877, OR = 0.425; 95% CI 0.194–0.935), marital status (OR = 5.682; 95% CI = 2.093–15.421, OR = 5.669; 95% CI = 1.448–22.198), place of residence (OR = 7.272; 95% CI = 4.231–12.499), and region of residence (OR = 11.515; 95% CI = 2.785–47.618) of males were found associated with health facility based delivery. Regarding policy to promote institutional delivery among women, these socio-demographic factors identified should be considered.